PROFIL PERFORMA ATLET DAYUNG KAYAK TEAM INDONESIA - Yasin, Syahid Nur; Azmara, Henry (Jurnal Olahraga, 2018)
Indonesian National Kayak Rowing. The sample in this study was the Indonesian national male rowing athlete who studied 19 people with an average age of 25 years, height 175 and weight 74. The research method used a survey using the Canoeing Protocol Test and the National Team TBR. The results of this study indicate the speed endurance test with a speed of Kayak 1000 meters in the air obtained values of 85% moderate and 95% good, the maximum strength test and maximum endurance of the chest and shoulder muscles obtained values of 75% moderate and 100% good, heart endurance, circulation blood and breathing with a 12-minute run show good grades. From the above average test results There are 2 good test scores, 1 test with 50% moderate and 50% good, 1 test with 40% good and 60% excellent, and good grades there is 1 test From the results of the assessment of the test components of Canoeing Test and TBR protocols can be taken on average based on the level of fitness of the Indonesian National Team Kayak Paddle athletes in the good category.